Ambroxol Upregulates Glucocerebrosidase Expression to Promote Neural Stem Cells Differentiation Into Neurons Through Wnt/β-Catenin Pathway After Ischemic Stroke - Ge, Hongfei; Zhang, Chao; Yang, Yang; Chen, Weixiang; Zhong, Jun; Fang, Xuanyu; Jiang, Xuheng; Tan, Liang; Zou, Yongjie; Hu, Rong; Chen, Yujie; Feng, Hua (Frontiers in Molecular Neuroscience, 2021)
Ischemic stroke has been becoming one of the leading causes resulting in mortality and adult long-term disability worldwide. Post-stroke pneumonia is a common complication in patients with ischemic stroke and always associated with 1-year mortality. Though ambroxol therapy often serves as a supplementary treatment for post-stroke pneumonia in ischemic stroke patients, its effect on functional recovery and potential mechanism after ischemic stroke remain elusive. In the present study, the results indicated that administration of 70 mg/kg and 100 mg/kg enhances functional recovery by virtue of decreasing infarct volume. The potential mechanism, to some extent, is due to promoting NSCs differentiation into neurons and interfering NSCs differentiation into astrocytes through increasing GCase expression to activate Wnt/β-catenin signaling pathway in penumbra after ischemic stroke, which advances basic knowledge of ambroxol in regulating NSCs differentiation and provides a feasible therapy for ischemic stroke treatment, even in other brain disorders in clinic.